LEXICAL AND CONTEXTUAL MEANINGS IN SONG LYRICS” MOANA ORIGINAL SOUNDTRACK”: PEDAGODICAL IMPLICATION - Sudar Sudar; Tusino Tusino; Beta Radish Charica Dewi (University of Kuningan, 2023)
This research aims to analyze song lyrics containing lexical and contextual meanings in the title of “Moana Original Soundtrack.